Ziziphus jujube promotes fertility and pregnancy outcomes in Rat model of uterine adhesions - Asgharzadeh, Fereshteh; Attarian, Mahsa; Khazaei, Majid; Al-Asady, Abdulridha Mohammed; Mansoori, Saeide; Naimi, Hamideh; Eskandari, Moein; Khorrami, Azar; Nazari, Seyedeh Elnaz; Aminian, Akram; Farazastanian, Marjaneh; Eshtad, Elaheh; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe therapeutic efficacy of oral administration of Ziziphus jujube in the context of uterine adhesion (UA) and its impact on pregnancy outcomes was investigated.MethodsIn a rat UA model, Z. jujube was evaluated for its ability to mitigate injury-induced uterine adhesion bands, uterine shortening, and enhance endometrial regeneration. The assessment included analysis of gland numbers, uterine endometrial thickness, and regulation of inflammatory cytokines. The antioxidant properties of Z. jujube were also studied through antioxidant enzyme activity in uterine tissue homogenates. Fibrotic changes were examined through histological Trichrome staining and analysis of pro-fibrotic factors.ResultsTreatment with Z. jujube resulted in a significant reduction in uterine tissue fibrosis, as evidenced by histological evaluation and reduced expression of fibrotic markers. The intervention demonstrated positive outcomes in embryonic development, pregnancy rates, and pregnancy outcomes. Z. jujube effectively inhibited the formation of extra-uterine adhesion bands to internal organs. No toxicity-related morphological changes were observed in vital organs of the Z. Jujube-treated group.DiscussionThe results collectively indicate that Z. jujube is a safe and potent natural product with anti-inflammatory and anti-fibrotic properties, highlighting its potential as a novel candidate for clinical studies targeting UA in patients.